Effects of graphene oxide on the strain-induced crystallization and mechanical properties of natural rubber crosslinked by different vulcanization systems. (29th August 2018) - Xie, Zheng-Tian; Luo, Ming-Chao; Huang, Cheng; Wei, Lai-Yun; Liu, Yu-Hang; Fu, Xuan; Huang, Guangsu; Wu, Jinrong
Abstract: To reveal the influence of graphene oxide (GO) on the mechanical properties of natural rubber (NR) crosslinked by different vulcanization systems, synchrotron radiation wide angle X-ray diffraction (WAXD) experiments were conducted to investigate the strain-induced crystallization (SIC) behaviors of the NR/GO nanocomposites. We found that the sulfur/accelerator (S/A) ratio in the vulcanization recipes is a critical factor which determines the SIC behaviors of the NR/GO nanocomposites: lower S/A ratio leads to higher crystallization rate of SIC. The tube model has been used to analyze the network structure of the NR/GO nanocomposites. The results demonstrate that the presence of GO more significantly increases the crosslinking density of the nanocomposites with lower S/A ratio. A possible mechanism has been proposed to interpret this phenomenon: during the curing process, the hydroxyl and carboxyl groups on the surface of GO could react with the vulcanization accelerator first and eventually form additional crosslinks in the vicinity of the GO sheets. This work may provide an instruction for developing GO filled rubber materials with superior mechanical properties. Graphical abstract: Image Highlights: Vulcanization system will affect the SIC behavior of graphene oxide filled rubber. Graphene oxide could react with curing agents to form crosslinks. Lower sulfur/accelerator ratio leads to higher crystallization rate of rubber composite.